Struktur dan dinamika sektor ekonomi perkotaan: analisis basis ekonomi kota Kotamobagu tahun 2018-2022 - Rifani, Irfan; Wenas, Richy Imanuel; Sangari, Imanuel Keygo; Leme, Renita; Putri, Anindya Puspita (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
Regional economic development requires understanding of economic structure and sectoral dynamics to formulate effective and sustainable policies. This study aims to analyze the economic structure and sectoral dynamics of Kotamobagu City by identifying base and non-base sectors and assessing their medium-term sustainability prospects. A descriptive quantitative approach was employed using Gross Regional Domestic Product (GRDP) data of Kotamobagu City and North Sulawesi Province at constant prices for the period 2018–2022. The analysis applied the Location Quotient (LQ) and Dynamic Location Quotient (DLQ) methods. The results indicate that Kotamobagu’s economy is dominated by service sectors, particularly public administration, financial services, social services, and construction, which function as base sectors. However, DLQ analysis reveals that not all base sectors exhibit sustainable growth prospects. Conversely, several non-base sectors demonstrate positive growth dynamics and potential role repositioning. These findings confirm that sectoral advantages are dynamic and cannot be adequately assessed using static approaches alone. This research provides a theoretical contribution to the development of regional economic analysis based on sectoral dynamics and serves as an empirical basis for the formulation of regional economic development strategies.